Seismic Fortification Analysis of the Guoduo Gravity Dam in Tibet, China. (5th May 2015) - Lin, Peng; Zheng, Wenwei; Huang, Bo; Zhang, Haichao
Abstract : The primary aim of this research was to analyze the seismic performance of the Guoduo gravity dam. A nonlinear FEM method was implemented to study the deformation, stress, and overall stability of dam under both static and dynamic loading conditions, including both normal and overloading conditions. A dam seismic failure risk control method is proposed based on the cracking mechanism induced by the dynamic load to ensure dam safety and stability. Numerical simulation revealed that (1) under normal static and dynamic loading the symmetry of the displacement distributions is good, showing that the dam abutments and riverbed foundation have good overall stiffness. The stress distribution is a safe one for operation under both normal water loading and seismic loading. (2) Attention should be paid to the reinforcement design of outlets of the diversion dam monoliths, and enhance the capability of sustaining that tensile stress of dam monoliths. (3) The shape of the dam profile has a significant effect on the dynamic response of the dam. (4) By employing the "overload safety factor method, " the overall seismic fortification is as follows:K 1 = 1.5, K 2 = 2 3, andK 3 = 3 4.